Internal Control Systems and Performance of Small and Medium Enterprises in Uganda: A Case Study of Katuna Town Council. - Mubangizi, Martin (Kabale University, 2023)
The purpose of the study was to establish the effect of internal controls on the financial performance of small and medium enterprises in the Katuna Town Council Kabale district. The study was guided by the following research questions; what is the relationship between internal controls and financial performance of SMEs in Katuna Town Council Kabale district? What is the effect of monitoring on the financial performance of SMEs in Katuna Town Council Kabale district? and how does risk assessment affect the financial performance of SMEs in Katuna Town Council Kabale strictly? The study adopted a descriptive research design. The study used a descriptive design which enabled the researcher to collect in depth information about the population being studied. This study focused on the population of employees who are in working with small and medium enterprises in Katuna Town Council. The target employees included the ones from the following departments, whole sellers, financial managers, money changers, and accountants. A population of 387 employees for the hundred SMEs in Katuna Town Council. This research used the probability technique and under this technique, the research specifically used the Stratified Random Sampling approach. A sample size of 116 employees was targeted for this particular study. The first research question sought to determine the relationship between internal controls on financial performance. The findings revealed that there is a positive and significant relationship between internal controls and financial performance. The second research question sought to determine the effect of monitoring on financial performance. The findings revealed that there was a positive and significant influence between monitoring and financial performance. The third research question sought to determine the effect of risk assessment on financial performance. The findings revealed that there was a positive and significant influence between risk assessment and financial performance. This study concludes that there exists a significant relationship between internal controls and financial performance. Internal control activities should highlight policies and procedures that help ensure management directives are carried out. They help to ensure that necessary actions are taken to address risks to the achievement of the entity's objectives. This study concludes that there is a significant and positive relationship between monitoring and financial performance. This study concludes that monitoring influences quality and effectiveness in the organization, the effectiveness of internal control systems, and audit reviews. This study recommends that SMEs should develop internal control systems that are in line with the financial performance of the organization. Internal controls will help the organization the organization in tracking its business performance including profitability, control, and effectiveness of the entire organization as a whole. This study recommends that SMEs should constantly monitor their financial performance by implementing audit reviews as well as performance reviews to make sure that organizational objectives are achieved accordingly.